The nature of the West Antarctic Rift System as revealed by noble gases in mantle minerals - Correale A.; Pelorosso B.; RIZZO, ANDREA LUCA; Coltorti M.; Italiano F.; Bonadiman C.; Giacomoni P. P. (Chemical Geology, 2019)
The noble gases He, Ne and Ar in fluid inclusions from mantle xenoliths at three localities in Northern Victoria Land (Baker Rocks, Greene Point and Handler Ridge), spanning about 300 km, provide new constraints on the nature of the lithospheric mantle beneath the West Antarctic Rift System (WARS). Mantle xenoliths are anhydrous and hydrous spinel-bearing lherzolite and harzburgite samples. The 4He/40Ar* ratios (0.004–0.39) in olivines, two pyroxenes and amphiboles are much lower than those typical of fertile mantle (1–5), suggesting that this lithospheric domain are consistent with a variably depleted mantle, as also indicated by the major- and trace-element compositions of whole rock and minerals. The 3He/4He ratios vary from 2.30 to 19.79 Ra. However, the lowest and highest 3He/4He ratios are related to the post-eruptive accumulation of radiogenic 4He and cosmogenic 3He, respectively. After filtering the data for these secondary effects, we constrain the 3He/4He signature of the subcontinental lithospheric mantle below this area to 7.1 ± 0.4 Ra (mean ± standard deviation). This isotope signature results from mantle metasomatism by asthenospheric melts with a MORB (mid-ocean ridge basalt)-type 3He/4He. The range of 7.1 ± 0.4 Ra is compatible with previous measurements in mantle xenoliths and lavas from other localities of the NVL, as far away as Mount Erebus, evidencing a homogeneous He-isotope signature beneath the entire rift. The He and Ne isotopes support the hypothesis that WARS origin is not related to a plume.